Sintesis dan Karakterisasi Polivinil Alkohol (PVA) Terlapis Polieugenol: Synthesis And Characterization of Polyvinyl Alcohol (PVA) Coated with Polyeugenol - Rahim, Erwin Abdul; Ridhay, Ahmad; Sitti Nur Halizah; Indriani; Sosidi, Husain; Khairuddin; Inda, Nov Irmawati; Nurakhirawati; Mirzan, Moh.; Amar, Aini Auliana (KOVALEN: Jurnal Riset Kimia, 2024)
A study has been conducted on materials containing polyvinyl alcohol (PVA) coated with poly eugenol. This research aims to explore the synthesis process and properties of PVA coated with poly eugenol. Characterization of PVA includes tensile strength measurement and surface observation using SEM. Additionally, the antioxidant activity of PVA was also tested using the DPPH method. In this study, PVA films were obtained by dissolving PVA in a water solvent. The characterization results indicate that the tensile strength ranges from 25.56 to 271.10 Mpa, elongation reaches 315.20 to 320%, and the young modulus ranges from 4.05 to 6.27 Mpa. Surface observation with SEM shows a smooth surface without pores. The antioxidant activity test shows IC50 values ranging from 84.11 to 175.37 ppm.